Pengaruh Pemberian Ekstrak Daun Sambiloto (Andrographis paniculata [Burm.F.] Ness) terhadap Kerusakan Struktur Histologis Sel Hepar Mencit yang Diinduksi Parasetamol - Heigy Mutiha Putri; Endang Listyaningsih S; Slamet Riyadi (Nexus Biomedika, 2013)
Background: Green chiretta contains andrographolide as active substances, flavonoids, saponins, and tannins which were thought to protect the livers cell from free radicals. In present study, Green chiretta leaves extract was evaluated for its protective effect on heksaklorosiklon-induced liver cell damage in mice. Methods: To evaluate the hepatoprotective effect of Green chiretta leaves extract, 28 male, Swiss Webster mice (Mus musculus) were equally divided into four groups. The group I (KK) were administered aquadest and group II (KP1) were not only administered aquadest but also a toxic dose of paracetamol on the day 12, 13 and 14. Grup IIIIV (KP2-KP3) were administered Green chiretta leaves extract (0.2 ml and 0.4 ml, successively) for 14 days and a toxic dose of paracetamol on the day 12, 13 and 14. Mice were sacrificed on the 15th day with neck dislocation and their livers were prepared for microscopy study to evaluate their cell damages. The damages were assessed by counting the number of hepatocyte on centrolobuler zone undergoing pyknosis, karyorhexis, and karyolysis. The data were analyzed using the One Way ANOVA test (? = 0.05) and the Post Hoc Multiple Comparisons (LSD) test (? = 0.05). Results: The mean liver cell damage score of the KP1 group was significantly higher (61.80 7.991) than the KK group (33.00 5.225). The KP2 group showed fewer numbers of liver cell damage (37.81 5.653) compared to the KP1 group (61.80 7.991) and the KP3 group (60.81 8.268). The One Way ANOVA test showed the significant difference between the four groups (p=0.000) while the LSD test showed the significant differences between each other group (p<0.005), except the group of KP1-KP3 (p> 0.005). Conclusions: The treatment of Green chiretta leaves extract was able to decrease the liver cell damage of mice. The increase dose of Green chiretta leaves extract was not followed by the increase of protection effect to the liver cell damage of mice induced by paracetamol. Keywords: Green chiretta leaves extract, paracetamol, liver cell histological damage.